2021
DOI: 10.1007/s10555-020-09946-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma and the epigenome

Abstract: Neuroblastoma (NB) is a pediatric cancer of the sympathetic nervous system and one of the most common solid tumors in infancy. Amplification of MYCN, copy number alterations, numerical and segmental chromosomal aberrations, mutations, and rearrangements on a handful of genes, such as ALK, ATRX, TP53, RAS/MAPK pathway genes, and TERT, are attributed as underlying causes that give rise to NB. However, the heterogeneous nature of the disease—along with the relative paucity of recurrent somatic mutations—reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 195 publications
(225 reference statements)
0
39
0
2
Order By: Relevance
“…Insight into the biology of NBL initiation and progression may help improve the survival of NBL patients. Previous studies have shown that MYCN amplification, copy number alterations, and rearrangements of oncology genes are putative causes contributing to NBL ( Fetahu and Taschner-Mandl, 2021 ). A large-scale study demonstrated that patients aged >18 months at diagnosis had a low survival rate ( Moroz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insight into the biology of NBL initiation and progression may help improve the survival of NBL patients. Previous studies have shown that MYCN amplification, copy number alterations, and rearrangements of oncology genes are putative causes contributing to NBL ( Fetahu and Taschner-Mandl, 2021 ). A large-scale study demonstrated that patients aged >18 months at diagnosis had a low survival rate ( Moroz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medulloblastoma is the most commonly seen embryonal tumor in children (approximately 25% of all brain malignancies in children), but it represents < 1% in adults (mainly in young adults < 40 years old) [76,77]. Neuroblastoma is another embryonic cancer involving the sympathetic nervous system that is mainly seen in infants and young children [78]. As metformin is only approved for the treatment of type 2 diabetes mellitus, which is not commonly seen in children, we have excluded patients aged < 25 years in the study (Figure 1).…”
Section: Limitationsmentioning
confidence: 99%
“…Many GWAS-defined neuroblastoma susceptibility genes have been identified including CASC15 , BRCA1 -associated RING domain protein 1 ( BARD1 ), LMO1 , DUSP12 , DDX4 , IL31RA , HSD17B12 , HACE1 , LIN28B , LINC00340 , LOC729177 ( FLJ44180 ), and NEFL . These genes display oncogenic or tumor-suppressive functions related to the disease (43) , (44) . The discovery of these susceptibility loci demonstrates the utility of analyzing GWAS signals for clues into the underlying biology driving neuroblastoma genesis.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%